Women’s Empowerment as It Relates to Attitudes Towards and Practice of Female Genital Mutilation/Cutting of Daughters: An Ecological Analysis of Demographic and Health Surveys From 12 African Countries - Coll, Carolina V. N.; Santos, Thiago M.; Wendt, Andrea; Hellwig, Franciele; Ewerling, Fernanda; Barros, Aluisio J. D. (Frontiers in Sociology, 2022)
Background: Women’s empowerment may play a role in shaping attitudes towards female genital mutilation/cutting (FGM/C) practices. We aimed to investigate how empowerment may affect women’s intention to perpetuate FGM/C and the practice of FGM/C on their daughters in African countries. Materials and methods: We used data from Demographic and Health Surveys carried out from 2010 to 2018. The countries included in our study were Benin, Burkina Faso, Chad, Côte d´Ivoire, Ethiopia, Guinea, Kenya, Mali, Nigeria, Senegal, Tanzania, and Togo. This study included 77,191 women aged 15–49 years with at least one daughter between zero and 14 years of age. The proportion of women who reported having at least one daughter who had undergone FGM/C as well as the mother’s opinion towards FGM/C continuation were stratified by empowerment levels in three different domains (decision-making, attitude to violence, and social independence) for each country. We also performed double stratification to investigate how the interaction between both indicators would affect daughter’s FGM/C. Results: The prevalence of women who had at least one daughter who had undergone FGM/C was consistently higher among low empowered women. Tanzania, Benin, and Togo were exceptions for which no differences in having at least one daughter subjected to FGM/C was found for any of the three domains of women’s empowerment. In most countries, the double stratification pointed to a lower proportion of daughters’ FGM/C among women who reported being opposed to the continuation of FGM/C and had a high empowerment level while a higher proportion was observed among women who reported being in favor of the continuation of FGM/C and had a low empowerment level. This pattern was particularly evident for the social independence domain of empowerment. In a few countries, however, a higher empowerment level coupled to a favorable opinion towards FGM/C was related to a higher proportion of daughters’ FGM/C. Conclusion: Women’s empowerment and opinion towards FGM/C seems to be important factors related to the practice of FGM/C in daughters. Strategies to improve women’s empowerment combined with shifts in the wider norms that support FGM/C may be important for achieving significant reductions in the practice.